Genomic, transcriptomic, and metabolic characterization of 2-Phenylethanol-resistant Saccharomyces cerevisiae obtained by evolutionary engineering - Holyavkin, Can; Turanlı-Yıldız, Burcu; Yılmaz, Ülkü; Alkım, Ceren; Arslan, Mevlüt; Topaloğlu, Alican; Kısakesen, Halil İbrahim and de Billerbeck, Gustavo and François, Jean Marie and Çakar, Z. Petek (Frontiers in Microbiology, 2023)
2-Phenylethanol is an aromatic compound commonly used in the food, cosmetic, and pharmaceutical industries. Due to increasing demand for natural products by consumers, the production of this flavor by microbial fermentation is gaining interest, as a sustainable alternative to chemical synthesis or expensive plant extraction, both processes relying on the use of fossil resources. However, the drawback of the fermentation process is the high toxicity of 2-phenylethanol to the producing microorganism. The aim of this study was to obtain a 2-phenylethanol-resistant Saccharomyces cerevisiae strain by in vivo evolutionary engineering and characterize the adapted yeast at the genomic, transcriptomic and metabolic levels. For this purpose, the tolerance to 2-phenylethanol was developed by gradually increasing the concentration of this flavor compound through successive batch cultivations, leading to an adapted strain that could tolerate 3.4 g/L of 2-phenylethanol, which was about 3-times better than the reference strain. Genome sequencing of the adapted strain identified point mutations in several genes, notably in HOG1 that encodes the Mitogen-Activated Kinase of the high-osmolarity signaling pathway. As this mutation is localized in the phosphorylation lip of this protein, it likely resulted in a hyperactive protein kinase. Transcriptomic analysis of the adapted strain supported this suggestion by revealing a large set of upregulated stress-responsive genes that could be explained in great part by HOG1-dependent activation of the Msn2/Msn4 transcription factor. Another relevant mutation was found in PDE2 encoding the low affinity cAMP phosphodiesterase, the missense mutation of which may lead to hyperactivation of this enzyme and thereby enhance the stressful state of the 2-phenylethanol adapted strain. In addition, the mutation in CRH1 that encodes a chitin transglycosylase implicated in cell wall remodeling could account for the increased resistance of the adapted strain to the cell wall-degrading enzyme lyticase. Finally, the potent upregulation of ALD3 and ALD4 encoding NAD+ -dependent aldehyde dehydrogenase together with the observed phenylacetate resistance of the evolved strain suggest a resistance mechanism involving conversion of 2-phenylethanol into phenylacetaldehyde and phenylacetate implicating these dehydrogenases.